STRATEGIES USED BY ENGLISH TEACHER FOR STUDENTS WITH SPECIAL NEEDS - Resa Hapitri (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
No one wants to be disabled or imperfect like other children. Being disabled doesn't mean they can't do anything. Thus, this research is focused on finding the strategies faced by English teachers in teaching students with special needs. The participant involved in this study is one of the English teachers in a special-needs school who has experience in teaching English. Data was collected using semi-structured interviews. The results show that the strategies used by teachers when teaching English are a student-centered approach and the use of repetition to help students remember lessons.